Occurrence and source analysis of polychlorinated naphthalenes in raw cow milk. (1st July 2022) - Dong, Shujun; Li, Jingguang; Zheng, Baiqin; Zhang, Lei; Zhang, Su; Zou, Yun; Wang, Yaxin; Fan, Mengdie; Wang, Ruiguo; Li, Yi; Wu, Yongning; Su, Xiaoou; et al.
Highlights: A total of 75 PCN congeners in raw cow milk from China were determined. PCN concentrations in cow milk could be influenced by PCN emission sources. PCNs in cow milk were dominated by lower chlorinated congeners. Silage acted as an important carrier for the migration of PCNs into cow milk. Chinese exposure risk to PCNs through the intake of cow milk is not significant. Abstract: The potential contamination of food items with polychlorinated naphthalenes (PCNs) has attracted increasing attention because of their toxicity, persistence and bioaccumulative characteristics. Humans are exposed to PCNs primarily through consuming animal-derived foodstuffs. However, the pathways by which PCNs can enter the food supplying chain are poorly understood. In this study, Σ75 PCNs were determined in raw cow milk (n = 82) collected from three different regions that varied in the intensity of PCNs emission sources in North China, using high-resolution gas chromatography/high-resolution mass spectrometry method. Higher PCN concentrations (214–2050 pg/g lw) were found in raw cow milk from dairy cow farms located in the region with relatively higher intensity of emission sources. Less chlorinated congeners were dominant in all raw cow milk samples. PCNs in cow milk might result from industrial fly ash emissions that contaminate animal feed through atmospheric deposition. Risks posed to humans through consuming PCNs in cow milk were low.